Da noção de livre arbítrio no âmbito do naturalismo biológico de Jhon Searle - Nascimento, Dácio José do (2022)
The present study aims to analyze the problem of free will in the Philosophy of Mind (biological naturalism) of the American philosopher John Searle. One of the preparatory conditions for a reflection on the problem of free will is the understanding of a set of interconnected notions, namely: the notion of consciousness, intentionality, and mental causation. Biological naturalism holds that mental phenomena are caused by neurobiological processes and are themselves characteristic of the brain. Consciousness, in Searle's view, is ontologically irreducible to neurobiological processes that occur at the base level of the brain system, even though it is caused and carried out within that same brain system. It is, in this sense, a mental property that emerges from neurophysiological processes of the brain and constitutes a characteristic of the system as a whole capable of producing mental states with the property of addressing objects, events and states of affairs in the world, i.e., having intentionality. It is essential to understand what Searle conjectures about mental causation. For him, it is incorrect to consider a conscious, intentional, and voluntary action of an agent to be the product of two independent sets of necessary and sufficient causes, the physical (from neurobiological processes), on the one hand, and the mental (from mental states), on the other hand. This would lead to the problem of causal supervenience. Furthermore, if we consider the principle of causal closure of the physical world, the necessary and sufficient causes for any event in the world are physical. This leads to the impotence of the mental, if it is considered as non physical (which is not the case with Searle, who rejects dualism). From a causal point of view, therefore, the causal efficiency of mental states, considered by Searle to be physical, does not exceed that of neurobiological processes. There is, therefore, a causal reduction. However, Searle argues that, from the ontological point of view, mental states (those of consciousness, above all) cannot be reduced to the neurobiological processes that underlie them, due to their subjective, first-person character. The question then arises: how can mental states have any relevance in our actions if they have no causal role? How could we explain our actions as being caused by our will, by our freedom to act, if there is a type of determinism, neurobiological? Searle thus introduces the theme of free will. For him, the experience of free will is evidenced when we perform actions consciously, intentionally, and voluntarily, because we always act under the assumption that we are free to perform the actions we decide. Searle explains voluntary actions in terms of reason. There is, according to him, a gap between the reasons for decision-making and actions, on the one hand, and decision-making and the effective performance of actions, on the other hand. It is considering this gap that he addresses and defends the notion of freedom to act or free will.